Extensão Universitária na América Latina e Formação de professores: uma abordagem a partir do XVII Congresso Latinoamericano y Caribeño de Extensión Universitaria - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The research focuses on University Extension in the context of teacher education in Latin America. Accordingly, the guiding question of the study is: what are the contributions of University Extension to teacher education in Latin America? It also considers some secondary questions, such as: what are the concepts and historical backgrounds of University Extension? What are the historical-ontological foundations in the academic education process in Latin America and the Caribbean? Which studies address University Extension in teacher education in Brazil? What are the perceptions of representatives (teachers, managers, coordinators, researchers, and rectors) from Latin American and Caribbean countries who participated in the XVII Congreso Latinoamericano y Caribeño de Extensión Universitaria regarding University Extension? Therefore, the general objective of this study is to analyze the contributions of University Extension to teacher education in Latin America and the Caribbean. Specifically, the objectives are to: historicize and conceptualize University Extension; discuss the historical-ontological foundations in the process of teacher education in Latin America and the Caribbean; present a systematic review of University Extension in teacher education in Brazil; investigate the perceptions of teachers, managers, coordinators, rectors, and university researchers from Latin American and Caribbean countries about University Extension. This research is applied, qualitative, bibliographic, documentary, and a case study. It uses some categories from Historical Dialectical Materialism for data analysis, such as totality (concrete, abstract, and contradiction), historicity, and ontology. Thematic analysis, according to Severino (2026), was used for data processing. The study references the works of Kochhann (2019, 2021, 2022), Forproex (2012), Faria (2001), Castro (2004), Souza (2000), Síveres (2013), Botomé (1996), Reis (1996), Jezine (2002), Gurgel (1986), Freire (2000), Tovar (2022), among others, as well as Laws, Resolutions, and Education and University Extension Plans from various Latin American countries. Data analysis reveals that University Extension is an educational, cultural, and scientific practice that integrates teaching and research, promoting interaction between the university and society. Extension activities significantly contribute to teacher education by providing practical and interdisciplinary experiences that connect teaching with social reality. However, the study highlights challenges in integrating these activities into curricula, emphasizing the need to overcome assistentialist practices and adopt critical and emancipatory approaches. It concludes that University Extension plays a fundamental role in teacher education but requires greater institutional engagement and a more integrated and critical approach to realize its transformative potential in Latin American and Caribbean social realities.
University Extension in Latin America and Teacher Education: an approach from the XVII Latin American and Caribbean Congress of University Extension
Keywords: Extensão Universitária; Formação de Professores; Transformação Social; América Latina e Caribe; University Extension; Teacher Education; Social Transformation; Latin America and the Caribbean; CIENCIAS HUMANAS::EDUCACAO; EDUCACAO::FUNDAMENTOS DA EDUCACAO